Law Enforcement on State Intelligence Strengthening in Countering Information System Hacking as a Threat to Sovereignty in North Sumatera - Krismanto Manurung; Muhammad Arif Sahlepi; Suci Ramadani (Journal Evidence Of Law, 2026)
This study aims to analyze law enforcement on strengthening state intelligence in an effort to counteract information system hacking as a form of cybercrime that has an impact on national stability and security. The research method used is normative juridical with a legislative and conceptual approach, through a study of relevant regulations such as the Law on Information and Electronic Transactions as well as provisions on state intelligence and cyber defense. The results of the study show that strengthening the state intelligence function, both through increasing the capacity of early detection, coordination between institutions, and optimizing the legal apparatus, is a crucial factor in preventing and overcoming information system hacking. However, there are still challenges in the form of limited resources, regulatory harmonization, and cross-sector collaboration. Therefore, continuous synergy is needed between law enforcement officials, intelligence agencies, local governments, and the community to strengthen the cybersecurity system as part of protecting state sovereignty in the digital era.